Differential expression profiles and functional prediction of circRNA in mice with traumatic heterotopic ossification - Wang, Zheng; Yi, Xinzeyu; Liu, Yuhang; Liu, Qiaoyun; Li, Zonghuan; Yu, Aixi (Frontiers in Immunology, 2023)
Background Traumatic heterotopic ossification (HO) is an intractable sequela incited by inflammatory insult. To date, the exact molecular mechanisms of traumatic HO formation remain unclear. Recent studies have indicated that circular RNAs (circRNAs) participate in various human skeletal diseases. Although the formation of HO recapitulates many programs during bone development and remodeling, few data are available concerning whether circRNAs could participate in this pathological osteogenesis. Methods To investigate the differentially expressed circRNAs (DE-circRNAs) in HO formation, microarray assay was performed to analyze the circRNA expression profile in four pairs of mice HO tissues and normal tissues. Then, qRT-PCR was applied to verify the microarray data. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses showed the biological functions of the differentially expressed circRNAs target genes. Cytoscape software was used to construct the circRNA–miRNA–mRNA network for circRNAs with different expression levels as well as the target genes. Results We demonstrated that 491 circRNAs were significantly differentially expressed in mouse HO tissues by a fold-change ≥ 2 and p-value ≤ 0.05. Among them, the expressions of 168 circRNAs were increased, while 323 were decreased. The expression levels of 10 selected circRNAs were verified successfully by qRT-PCR. GO analysis exhibited that these DE-circRNAs participated in a series of cellular processes. KEGG pathway analysis revealed that multiple upregulated and downregulated pathways were closely related to the DE-circRNAs in HO mice. The circRNA-miRNA-mRNA networks demonstrated that DE-circRNAs may be involved in the pathological osteogenesis of HO through the circRNA-targeted miRNA-mRNA axis. Conclusion Our study first demonstrated the expression profiles and predicted the potential functions of DE-circRNAs in mice traumatic HO, which may shed new light on the elucidation of mechanisms as well as provide novel potential peripheral biological diagnostic markers and therapeutic targets for traumatic HO.